Dietary camellia seed oil attenuates liver injury in mice chronically exposed to alcohol - Guo, Rui; Zhu, Jinyan; Chen, Lin; Li, Jiaomei; Ding, Qinchao; Han, Qiang; Zheng, Weijun; Li, Songtao (Frontiers in Nutrition, 2022)
Dietary fat composition is closely associated with the pathological development of alcoholic liver disease (ALD). Fat enriched with saturated fatty acids protects whereas with polyunsaturated fatty acids aggravates alcohol-induced liver injury. However, limited study has addressed how monounsaturated fatty acids (MUFAs) determines the pathological process of ALD. Our study was conducted to evaluate the effect of MUFAs-enriched-camellia seed oil (CSO) on alcohol-induced liver injury. The ALD model was established by feeding C57BL/6 mice with Lieber-DeCarli diet, and with either CSO or polyunsaturated fatty acids (PUFAs)-enriched-corn oil (CO) as fat source. After 4-week-intervention, CSO-feed rescued alcohol-induced liver injury compared to CO-feed, evidenced by measurements of plasma ALT activity, H&E stain, and hepatic cleaved-Caspase-3 expression. Besides, CSO-feed alleviated alcohol-induced oxidative stress, associated with NRF2 and Hif-1α expressions improvement. The reduction of F4/80 immunostaining and the decreased expressions of hepatic TNF-α and IL-6 suggested CSO-feed improved alcohol-induced inflammation. The mechanistic analysis showed that the inhibition of ASK1 and MAPKs might contribute to CSO-protected liver injury. Notably, we observed CSO-feed relieved the gut microbiota disturbance with the decreased Firmicutes and Turicibater, and the increased Bacteroidota, Alloprevotella, and Bacteroides, and reduced circulatory endotoxin level and lipolysis of adipose tissue, which are the known pathogenic factors in alcohol-induced liver injury. Unexpectedly, CSO induced more hepatic steatosis than CO-feed. In conclusion, CSO attenuated chronic alcohol consumption-induced liver injury but enhanced hepatic steatosis. CSO could be a potential dietary choice for alcoholic individuals with liver injury.